Níveis séricos de CSF-1 e Ang-2: parceiros no prognóstico e diagnóstico de Cancro do Pulmão de Células Não-Pequenas - Ana Luísa Pequeno Coelho (2018)
Lung cancer is the most incident and lethal form of cancer, with late diagnosis as a major determinant of its bad prognosis. Immunotherapies targeting immune checkpoints improve survival, but positive results encompass only 30-40% of the patients, possibly due to alternative pathways to immunosuppression, including tumor associated macrophages (TAM). CSF-1 is implicated in TAM differentiation and recruitment to tumors and in tumor angiogenesis, through a special setting of Tie-2-expressing macrophages, which respond to Angiopoietin-2 (Ang-2). We evaluated the role of serum levels of CSF-1 in NSCLC prognosis and whether these could serve as biomarkers for NSCLC detection, along with Ang-2.We prospectively studied an unselected cohort of 145 NSCLC patients and a group of 30 control individuals. Serum levels of Ang -2 and CSF-1 were measured by ELISA prior to treatment. Serum levels of CSF-1 and Ang-2 are positively correlated (p<0.000001). Individuals with high serum levels of CSF-1 present a seventeen-fold risk for NSCLC development and patients with combined High Ang-2/CSF-1 serum levels present a 5-fold increased risk of developing NSCLC. High Ang-2/CSF-1 phenotype is also associated with worst prognosis in NSCLC. Combined expression of CSF-1 and Ang-2 seems to contribute to worst prognosis in NSCLC and it is worthy to understand the basis of this unexplored partnership. Moreover, we think CSF-1 could be included as a biomarker in NSCLC screening protocols that can improve the positive predictive value of the current screening modalities, increase overall cost effectiveness, and potentially improve lung cancer survival.